PENGGUNAAN MEDIA KARTU HURUF DALAM MENINGKATKAN MEMBACA PERMULAAN SISWA KELAS I DI SDN 186/I SRIDADI - Rifda, Ridfa Afifah; Novia, Novia Mahera Shafitri; valin, Valina Julia Cahyani; Destrinelli, Destrinelli; Risdalina, Risdalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the early reading skills of first-grade students at SDN 186/1 Sridadi through the use of letter card media. The research method employed is Classroom Action Research (CAR) based on the Kurt Lewin model, which consists of two cycles, each comprising four stages: planning, action, observation, and reflection. The research subjects were 8 first-grade students. Data collection techniques included observation, interviews, documentation, and tests. The results showed that the use of letter card media could enhance students' early reading skills, as evidenced by improvements in pronunciation accuracy, reading fluency, voice clarity, intonation, and comprehension. The percentage of learning mastery increased from 50% in the pre-action phase to 75% at the end of the first cycle, and 80% at the end of the second cycle. In conclusion, letter card media is effective for teaching early reading in lower elementary school grades.